Social calls of big brown bats in a competitive feeding context - Fry, Reese N.; Suong, Emily; Simmons, James A.; Simmons, Andrea Megela (Frontiers in Ecology and Evolution, 2025)
Big brown bats (Eptesicus fuscus) have a diverse vocal repertoire. We tested the hypothesis that frequency-modulated bouts (FMBs) are male-specific calls produced during food competition. Seven pairs of bats (male-male, male-female, female-female) competed in the laboratory to capture a food item. Within this restricted behavioral context, we identified six common social call types, broadly classified as aggressive in previous literature. Female-female pairs produced significantly fewer calls than the pairs containing males, and their social calls were longer in duration. FMB calls were absent in all female-female pairs but were present, in varying numbers, in pairs containing males. FMBs recorded in the laboratory resembled those recorded from big brown bats foraging in the wild. Results support the hypothesis that FMBs are produced in foraging interactions in both the laboratory and the field, and confirm previous reports of less robust vocal interactions between female bats.